2020
DOI: 10.3390/su12124952
|View full text |Cite
|
Sign up to set email alerts
|

Performance Prediction of Proton Exchange Membrane Fuel Cells (PEMFC) Using Adaptive Neuro Inference System (ANFIS)

Abstract: This investigation explored the performance of PEMFC for varying ambient conditions with the aid of an adaptive neuro-fuzzy inference system. The experimental data obtained from the laboratory were initially trained using both the input and output parameters. The model that was trained was then evaluated using an independent variable. The training and testing of the model were then utilized in the prediction of the cell-characteristic performance. The model exhibited a perfect correlation between the predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…This is ascertained by non-uniform current distribution when the RH is varied from 95% to 70%. 22 Related work by Wilberforce et al 23 shows similar effects exhibited by back pressure and air stoichiometry.…”
Section: Effect Of Relative Humiditymentioning
confidence: 70%
See 2 more Smart Citations
“…This is ascertained by non-uniform current distribution when the RH is varied from 95% to 70%. 22 Related work by Wilberforce et al 23 shows similar effects exhibited by back pressure and air stoichiometry.…”
Section: Effect Of Relative Humiditymentioning
confidence: 70%
“…In 2016, Zhang et al 23 identified certain key parameters that are important for the development of fuel cell with homogeneity, overall stability, performance and resistance losses. They reported that water management and reactant gas concentration are the vital parameters for an efficient fuel cell.…”
Section: Design Parameters and Their Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 2, shows the typical polarization curve of proton exchange membrane FC (Wilberforce and Olabi, 2020). Turbochargers belong to the aerodynamic compressors, while other compressors (or mechanical paddles) belong to the volumetric compressors (Robison and Beaty, 1992), the important criteria for choosing a compression system suitable for the FCV application listed and compared in the form of weighting and rating matrix.…”
Section: Fig 1 Fc System Flow Diagrammentioning
confidence: 99%
“…To better understand the functionality of this system, Figure 3 gives an example of two inputs and one output. 31 Experimental study…”
Section: Layermentioning
confidence: 99%